Resolução da estrutura tridimensional de uma lectina de sementes de Canavalia grandiflora Benth. com efeitos sobre mecanismos inflamatórios - Barroso Neto, Ito Liberato (2010)
Plant Lectins can be defined as non-immune origin proteins having at least one non-catalytic domain that binds reversibly in a specific fashion to a mono-or oligosaccharide. The legume lectin family group represents the best studied of these proteins, in particular highlighted the subtribe Diocleinae, which has the best characterized representative, ConA. Lectins Diocleinae show a high degree of structural similarity, but the same does not regarding biological activities and specificity to different carbohydrates, which makes it important to research in structural and biological levels of its various members, among them the Canavalia grandiflora Benth. The lectin from Canavalia grandiflora (Congr) was purified according to Ceccato (2001) and was crystallized by vapor diffusion method at 293 K. Crystals were obtained in a state containing 0.5 M of cadmium sulfate hydrate, 0.1 M HEPES pH 7.5 and 1.0 M sodium acetate trihydrate. The crystals have the orthorhombic space group I222, the unit cell has the dimensions a = 67.70 Å, b = 55.90 Å and c = 107.46 Å and angles? =? =? = 90 °, giving a monomer in the asymmetric unit and a content of 42.53% solvent in the crystal. The structure was solved to 2.19 Å and phase problem was solved by the method of molecular replacement using the coordinates of Canavalia gladiata as a template (PDB: 2D7F). The refinement showed satisfactory "rfactor" and "Rfree" with 22.6 and 27.4 respectively and only one amino acid residue in a region of the Ramachandran disallowed. Despite the high structural similarity, small changes in the direction of key amino acids may be responsible for the diversity in the biological applications as a result of the residues of the carbohydrate binding site which are retained despite changes in spatial orientation. The primary sequence of the lectin from C. grandiflora has great similarity with lectins of the same genus, but it has the largest number of mutations representative of the genus Dioclea, characterizing it as the subgenus Canavalia nearest Dioclea and canavalias is among the most primitive. The Congregation edamatogênica showed activity in a model of paw edema (sc) and relaxing effect on smooth muscle of rat aorta endothelial, but the effects appear to be weak compared to other lectins Diocleinae.